The impact of chronic fentanyl administration on the cerebral cortex in mice: Molecular and histological effects - Ayman Alzu'bi (18192898) (2024)
Purpose Fentanyl, a fully synthetic opioid, is widely used for severe pain management and has a huge abuse potential for its psychostimulant effects. Unlike other opioids, the neurotoxic effects of chronic fentanyl administration are still unclear. In particular, little is known about its effect on the cerebral cortex. The current study aims to test the chronic toxicity of fentanyl in the mice model. Methods Adult male Balb/c mice were chronically treated with low (0.05 mg/kg, i.p) and high (0.1 mg/kg, i.p) doses of fentanyl for 5 consecutive weeks, and various neurotoxic parameters, including apoptosis, oxidative stress, and neuroinflammatory response were assessed in the cortex. Potential histological as well as neurochemical changes were also evaluated. Results The results of this study show that chronic fentanyl administration induced intense levels of apoptosis, oxidative stress, and neuroinflammation in the cerebral cortex. These findings were found to be correlated with histopathological characteristics of neural degeneration and white matter injury. Moreover, fentanyl administration was found to reduce the expression of both NMDA receptor subunits and dopamine receptors and elevate the level of epidermal growth factor (EGF). Conclusion Fentanyl administration induced neurotoxic effects in the mouse cerebral cortex that could be primarily mediated by the evoked oxidative-inflammatory response. The altered expression of NMDA receptors, dopamine receptors, and EGF suggests the pernicious effects of fentanyl addiction that may end in the development of toxic psychosis. Other Information Published in: Brain Research Bulletin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.brainresbull.2024.110917